Avalon - Seton, Anya (Houghton Mifflin Company, 1965)
The last quarter of the tenth century was a time of conflict and exploration. While the Anglo-Saxons fought against the Vikings, Norsemen voyaged into the unknown, looking for new lands to pillage, and so discovered America. Prince Rumon of France, descendant of Charlemagne and King Alfred, was a searcher. He had visions of the Islands of the Blessed, perhaps King Arthur's Avalon "where falls not hail, or rain, or any snow." Merewyn grew up in savage Cornwall-a lonely girl, sustained by stubborn courage and belief in her descent from great King Arthur. Chance-or fate-in the form of a shipwreck off the Cornish coast brought Rumon and Merewyn together and from that hour their lives were intertwined. Bound by his vow to her dying mother, Rumon brought Merewyn safely to England and kept from her and all others the shameful secret of her birth. But there his responsibility ended. At court Queen Alfrida dazzled him with her beauty and held him in subjection to her will. Freed by the revelation of Alfrida's murderous actions in a bid to capture the throne for her son, Rumon finally turned to Merewyn, only to find that he had lost her. His search led him across the Atlantic to an unknown land, to disappointment, and at last to fulfillment and peace.